IMPLIKASI PENCABUTAN HAK ATAS TANAH TERHADAP PERLINDUNGAN HAK ASASI MANUSIA - Faturrahim Faturrahim (UNISSULA, 2015)
Ownership of land rights is a fundamental right that is also a part of human rights. Revocation of ownership of land rights by the president is done for the public interest. The protection of subjects' rights to the right to repeal of rights is based on an understanding of the common sense. Public interest is an abstract, easily understood theoretically, but becomes very complex when implemented.